Voter Turnout in European Parliament Elections: A Spatial Analysis - Nadia Fiorino; Nicola Pontarollo; Roberto Ricciuti (Center for Economic Studies and ifo Institute (CESifo), 2016)
In European Parliament elections turnout rates, traditionally lower than in national parliamentary elections, decrease from one elections to the next, and show strong variations within and between countries. What explains this decline? Why are there such big differences between and within the EU member countries? This paper investigates these problems by analyzing the last four EP elections in the EU-13, for 156 regions. We first study the spatial features of turnout and subsequently test a Hierarchical Linear Model to assess the impact of some socio-economic, institutional and political factors on voter turnout. The results confirm the spatial dependence of data and indicate a significant role of compulsory voting, domestic political cleavages, and uncertainty on the labor market. No evidence is found that European financial transfers, GDP per capita or unemployment influence turnout. Finally, the oldest segment of population seems more prone to vote than the youngest part.
Keywords: 330; European Parliament elections; voter turnout; subnational variation; Hierarchical Linear Model